PROFESSIONAL COMPETENCY OF VOCATIONAL TECHNICAL SCHOOL PRINCIPAL - Lunyachek V.E. (Pressing Problems of Public Administration, 2018)
The paper explores the issues of evaluating professional competency of vocational technical schools principals in the context of reforming the entire area. The emphasis is laid on the need for development of a uni ed system for evaluation of their professional competency in accordance with the relevant structure. It is proposed to conduct the evaluation according to regulatory, scienti ctheoretical, human resource, methodological, and IT units. Samples of some test assignments are given. The paper also highlights the idea that evaluation of professional competency of vocational technical schools principals should be a mandatory condition for their appointment to the post and participation in a regular attestation. A focus is brought on the necessity for a systemic consideration of the issues addressed in the paper at scienti c-theoretical communicative events and administrative meetings as an important prerequisite of further positive development of the entire field. The matter of the relevance of developing modern models of vocational technical education administration has also been made actual as an important condition of the education system reform.